Chaotic Justice : Rethinking African American Literary History. - Ernest, John (Book collections on Project MUSE., 2009)
Ernest revisits the work of 19th-century writers and activists such as Henry "Box" Brown, Frederick Douglass, Harriet Wilson, William Wells Brown, and Sojourner Truth, demonstrating that their concepts of justice were far more radical than those imagined by most white sympathizers. He offers new principles of justice that grant fragmented histories, partial recoveries, and still-unprinted texts the same value as canonized works. His proposal is both a historically informed critique of the field and an invigorating challenge to present and future scholars of African American literatur